VD_FINDINFO AI 160/13 - 187/2014 vom 17. Juli 2014 - VD Tribunal cantonal (2014)
MOYEN AUXILIAIRE, LUNETTES, MESURE MÉDICALE DE RÉADAPTATION, INFIRMITÉ CONGÉNITALE | 12 LAI, 13 LAI, 21 al. 1 LAI, 8 LAI